Kepastian Hukum dalam Undang-undang Minerba - Yuking, Ana Sofa (Pelita Harapan University, 2011)
Law Number 11 of 1967 concerning Basic Provisions of Mining is no longer current. Therefore, revision of laws and regulations in the field of mineral and coal mining is required in order to manage and seek potential minerals and coal in an independent, reliable, transparent, competitive, efficient and environmentally sound manner and to sustainably assure national development. A fundamental change from Law Number 4 of 2009 is the changing in the management of mineral and coal mines from contracts of works and coal contracts of works that previously placed the government in equal position with Mining Investors as Civil Law subjects. Now, the law has switched to a Licensing System. The Government is no longer placed alongside Mining Investors; the government is currently acting as the authority to grant Mining Permits. The authority shall be exercised under provisions of laws and regulations which impose legal consequences on both Mining Investors and the government as the licensing authority. Regarding the governmentâs position as regulator, there is an inconsistency in the divestment policy of Law number 4 of 2009. The government still obliges foreign parties to divest their shares to the government as the priority; rightfully, the obligation of share divestment should be addressed to BUMN or BUMD. Transitional provisions in Law number 4 of 2009 regulate that contracts of works and coal contracts of works that already exist prior to the effectiveness of this Law shall remain valid until the contracts/agreements expire, with the provision that all articles that are contained in contracts of works and coal contracts of works must be adjusted to the Law with the exception of state revenues. Mining Concessions (or Kuasa Pertambangan) that already exist prior to the effective date of this law, based on Government Regulation Number 23 of 2010, shall remain valid, but should be adjusted into Mining Permits (or Ijin usaha Pertambangan).